Electrochemical and theoretical evaluation of the interaction between dna and amodiaquine: evidence of the guanine adduct formation - Arguelho, Maria Lara P. M.; Alves, José do Patrocínio H.; Stradiotto, Nelson Ramos [UNESP]; Lacerda Júnior, Valdemar; Pires, José Maria; Beatriz, Adilson (Sociedade Brasileira de Química, 2010)
The electrochemical behavior of the interaction of amodiaquine with DNA on a carbon paste electrode was studied using voltametric techniques. In an acid medium, an electroactive adduct is formed when amodiaquine interacts with DNA. The anodic peak is dependent on pH, scan rate and the concentration of the pharmaceutical. Adduct formation is irreversible in nature, and preferentially occurs by interaction of the amodiaquine with the guanine group. Theoretical calculations for optimization of geometry, and DFT analyses and on the electrostatic potential map (EPM), were used in the investigation of adduct formation between amodiaquine and DNA.
Keywords: amodiaquine; guanine; adduct